The Effect of Organizational Culture and Organizational Commitments on Employee Performance at the Representative Office of Bank Indonesia in Bengkulu Province - Ulfa Zahara; Suwarni Suwarni; Nurzam Nurzam (Fakultas Ekonomi Universitas Dehasen Bengkulu, 2022)
Good performance can be seen from the work that can be achieved by an employee. If the results of an employee's work are good and in accordance with established procedures, the goals will be achieved. This study aims to determine the effect of organizational culture and organizational commitment on employee performance at the Representative Office of Bank Indonesia in Bengkulu Province. The sample in this study was 46 permanent employees at the Representative Office of Bank Indonesia in Bengkulu Province. Collecting data using a questionnaire and the analytical method used is multiple linear regression, determination test and hypothesis testing. The results of the regression analysis show Y = 7,828 + 0,386X1 + 0,445 X2, + 4,596 this describes a positive regression direction, meaning that there is a positive effect between X1 (organizational culture) and X2 (organizational commitment) on performance (Y). It means that if the variables of organizational culture and organizational commitment increase, it will increase performance. The value of the coefficient of determination is 0.557. This means that X1 (organizational culture) and X2 (organizational commitment) affect performance (Y) by 55.7% while the remaining 44.3% is influenced by other variables not examined in this study. 0.05 explains that partially organizational culture variables and organizational commitment have a significant effetc on employee performance variables at the Representative Office of Bank Indonesia in Bengkulu Province, the significant value is less than 0.05. The results of the F test at a significance level of 0.05 explain that the organizational culture variable and organizational commitment have a significant simultaneous effect on employee performance at the Representative Office of Bank Indonesia in Bengkulu Province because the significant value is smaller than 0.05..